Paradigm shift in health-care seeking behavior: A report from central Kerala, India, during COVID-19 pandemic - Kezia Kuruvilla; Praveenlal Kuttichira; Pulikkottil Raphael Varghese; Elamthuruthy Vilson Vinu; Indu K Gopi (Wolters Kluwer Medknow Publications, 2020)
Context: Coronavirus is a novel public health problem, which has influenced the mindset of people and restricted the community mobility. These changes influence the health-care seeking behavior of people. Aim: This study analyzes the changing trend in patients coming for hospital based non-COVID care in the context of COVID-19. Settings and Design: This is a retrospective study based on hospital records of patients attending a tertiary care center, attached to a private medical college. Materials and Methods: Age, gender, and department wise daily registrations of patients from January 1 to June 30 of 2 consecutive years, 2019 and 2020 were considered, with new and review cases noted separately. Statistical Analysis Used: Data analyzed using Excel 2007. Results: The number of patients seeking hospital-based care during the year 2020 decreased by 31.01% compared to 2019 (P < 0.001). Maximum patient fall was noticed in the month of April. Patient decline was highest in the age group ≤14 (37.22%) and least in the senior citizen group (29.26%). The outpatient departments showed higher fall percentage (31.52%) compared to emergency services (26.65%), with highest fall in pediatrics (40.76%) and minimum in surgical allied super specialty (20.04%). Conclusions: A fall in patients occurred during COVID-19 and the associated restrictions implemented to contain the virus, which might be the result of an altered approach to morbidity and health care. This will disrupt the health care services to the vulnerable groups with complex health needs, influencing their health outcome in the long run.